Barriers to Health-Care Access: A Case Study of Bangladeshi Temporary Migrant Workers in Kuala Lumpur, Malaysia - Md Sayed Uddin; Muhammad Mehedi Masud; Qazi Muhammad Adnan Hye (2020)
The primary objective of this study was to identify the barriers to accessing health-care services as perceived by Bangladeshi temporary workers’ in Kuala Lumpur, Malaysia. The participants comprised 300 migrants working in the construction, manufacturing, and service sectors from three areas of Kuala Lumpur with the highest concentration of Bangladeshis. Following an analysis of the face-to-face structured interviews, the findings indicated that the main barriers were health-care providers not understanding migrant workers’ health problems, high medical costs, self-medication, and lack of transportation. It is recommended, therefore, that a pre-departure orientation program should be developed to familiarize migrant workers with the Malaysian health-care system and procedures, as well basic courses in Malay (Bahasa Melayu) and English, to help them access and use health-care services. In addition, it is suggested that a further, larger study is conducted to extend the findings to other states in Malaysia where there are Bangladeshi temporary migrant workers from similar backgrounds.